Espaço público e movimento Hip Hop: batalhas de MCs, identidade, sociabilidade e cidadania em Belém, Pará - BATALHA, Eryck de Jesus Furtado (Universidade Federal do Pará, 2019)
Currently the Hip Hop Movement in Belém, Pará, have occupying the public space more presently through the battles of MCs that are held in public squares throughout the city. In this work we intedd to understand how the action of these battles, in public spaces of Belém, represent a reference to the struggle for citizenship. To achieve this goal we seek, through the concepts of public space, social movements, identity, socibility and citizenship, analyze the actions of the subjects that make up these battles, the senses that their attach to the space, their relationship with others groups, their goals and motivations. We conduct a field work guided by an ethnographic perspective that allowed us to raise pertinent data to our issues and understand that the presence of hip hop in the public spaces of the city changes both within the movement, educating and forming citizens aware, as in the spaces it occupies, promoting dialogue with other groups and encouraging the presence of differences in public space